2021
DOI: 10.5415/apallergy.2021.11.e19
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and monthly variation in peak expiratory flow rate in children with asthma

Abstract: Background Although understanding the seasonal patterns of asthma deterioration is important to prevent asthma exacerbation, previous approaches have limitations in evaluating the actual trend of asthma exacerbation. Objective This study aimed to evaluate the seasonal and monthly variations in the peak expiratory flow rate (PEFR) among children with asthma. Methods A total of 89 patients with asthma were enrolled between December 2012 and Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A study ascertain the seasonal patterns of asthma exacerbation by recording the percentage change in PEFR from baseline. They concluded that PEFR in children with asthma was lower in autumn than in winter (20). The PEFR was significantly reduced in April and October than in January.…”
Section: 3 and 4)mentioning
confidence: 97%
“…A study ascertain the seasonal patterns of asthma exacerbation by recording the percentage change in PEFR from baseline. They concluded that PEFR in children with asthma was lower in autumn than in winter (20). The PEFR was significantly reduced in April and October than in January.…”
Section: 3 and 4)mentioning
confidence: 97%